Pendapatan asli desa dan pemberdayaan masyarakat: pengaruh terhadap kesejahteraan dengan moderasi jumlah penduduk - Melathi, Harum; Darmanto , Darmanto; Pratiwi, Desy Nur (Nur Science Institute, 2024)
This research examines the influence of Village Original Income and Community Empowerment on Community Welfare by considering Population as a moderating variable, using a case study in Manjungan Village, Ngawen District. This quantitative research was conducted with a population from Manjungan Village, Ngawen District, Klaten Regency. The sample was selected using the Slovin formula, with 96 respondents. Primary data was obtained through questionnaires, and data analysis was carried out using multiple linear regression. The test results show that Village Original Income and Community Empowerment significantly positively affect Community Welfare. However, population size does not strengthen the relationship between the village's original income and community welfare, while population size moderates the relationship between community empowerment and welfare.